1998
DOI: 10.1292/jvms.60.1329
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Viral Effect of Interferon-.ALPHA. on Bovine Viral Diarrhea Virus.

Abstract: ABSTRACT. To get basic information to control persistent virus infection among domestic animals by cytokines, the antiviral activity of four natural human cytokines against bovine viral diarrhea virus (BVDV) was evaluated. Normal bovine peripheral blood mononuclear leukocytes (PBML) and fetal bovine muscular cells (FBMC) were treated with varying doses of human interferon (IFN)-α, IFN-γ, tumor necrosis factor (TNF)-α and TNF-β. The antiviral activity in treated cells was measured by the titration of virus infe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
12
0
3

Year Published

2002
2002
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 16 publications
4
12
0
3
Order By: Relevance
“…We know that viruses can compromise the elaboration of IFN action: over recent years several examples of viruses that inhibit IFN signaling have been described (16). It is known that both cp and ncp BVDV are sensitive to IFN (5,35), and it is consistent with these observations that the titration of bovine IFN on ncp BVDV-infected cultures is identical to that observed in control cultures. These results indicate that ncp BVDV cannot compromise IFN signaling and extend recently published results of studies using an antiviral assay (34).…”
Section: Discussionmentioning
confidence: 80%
See 2 more Smart Citations
“…We know that viruses can compromise the elaboration of IFN action: over recent years several examples of viruses that inhibit IFN signaling have been described (16). It is known that both cp and ncp BVDV are sensitive to IFN (5,35), and it is consistent with these observations that the titration of bovine IFN on ncp BVDV-infected cultures is identical to that observed in control cultures. These results indicate that ncp BVDV cannot compromise IFN signaling and extend recently published results of studies using an antiviral assay (34).…”
Section: Discussionmentioning
confidence: 80%
“…In contrast to the sensitivity of BVDV to IFN, it has been reported that TNF-␣ has no antiviral effect on cp or ncp BVDV in culture (5,35), which might suggest that TNF-␣ signaling is compromised in BVDV-infected cells. TNF-␣ signals through a series of receptors and kinases that result in the phosphorylation and proteasome degradation of the inhibitor of NF-B, IB, resulting in NF-B transport to the nucleus of the cell (31).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Current treatment for HCV infection is (pegylated) IFN-␣ either alone or in combination with ribavirin (23). The HCV replicon has been shown to be sensitive to IFN-␣, -␤, and -␥ (7), and BVDV is known to be interferon sensitive (6,32). We compared the sensitivity of the Huh-7-BVDV and Huh-7-HCV replicons against IFN-␣, -␤, and -␥ (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…BVDV has long been known to block the activity of endogenous interferon (10), but exogenously added interferons have been shown to inhibit the replication of vesicular stomatitis virus even when the cells have been coinfected with ncpBVDV (31). Human interferons, not surprisingly, have demonstrated poor activity against BVDV in bovine cells (32). We examined the effect of various human interferons on BVDV and HCV RNA replication in the same human cellular background and found that both replicons had similar susceptibilities to the interferons.…”
Section: Discussionmentioning
confidence: 99%